2021
DOI: 10.3390/cancers13071670
|View full text |Cite
|
Sign up to set email alerts
|

Furin Prodomain ppFurin Enhances Ca2+ Entry Through Orai and TRPC6 Channels’ Activation in Breast Cancer Cells

Abstract: The intracellular calcium concentration ([Ca2+]i) modulation plays a key role in the regulation of cellular growth and survival in normal cells and failure of [Ca2+]i homeostasis is involved in tumor initiation and progression. Here we showed that inhibition of Furin by its naturally occurring inhibitor the prodomain ppFurin in the MDA-MB-231 breast cancer cells resulted in enhanced store-operated calcium entry (SOCE) and reduced the cell malignant phenotype. Expression of ppFurin in a stable manner in MDA-MB-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 56 publications
(117 reference statements)
3
8
0
Order By: Relevance
“…Provocatively, these dichotomous proliferative and migratory responses to inflammatory conditions may represent a point of vulnerability to be exploited by PEMF-based therapies in order to mitigate the invasiveness of breast cancer cells. PEMF exposure attenuates the proliferative and migratory capacities of breast cancer cells in positive correlation to TRPC1 channel expression ( Figures 5 and 7 ), aligning with evidence that catalytic activation of TRPC6, similarly implicated with proliferation and inflammatory responses in breast cancer, attenuates MDA-MB-231 breast cancer cell viability and migratory capacity ( 51 ). Both studies further demonstrated reductions in breast cancer cell invasiveness in response to activation of either TRPC1 (PEMF exposure) ( Figure 7D ) or TRPC6 (Furin inhibition) ( 51 ).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Provocatively, these dichotomous proliferative and migratory responses to inflammatory conditions may represent a point of vulnerability to be exploited by PEMF-based therapies in order to mitigate the invasiveness of breast cancer cells. PEMF exposure attenuates the proliferative and migratory capacities of breast cancer cells in positive correlation to TRPC1 channel expression ( Figures 5 and 7 ), aligning with evidence that catalytic activation of TRPC6, similarly implicated with proliferation and inflammatory responses in breast cancer, attenuates MDA-MB-231 breast cancer cell viability and migratory capacity ( 51 ). Both studies further demonstrated reductions in breast cancer cell invasiveness in response to activation of either TRPC1 (PEMF exposure) ( Figure 7D ) or TRPC6 (Furin inhibition) ( 51 ).…”
Section: Discussionsupporting
confidence: 79%
“…PEMF exposure attenuates the proliferative and migratory capacities of breast cancer cells in positive correlation to TRPC1 channel expression ( Figures 5 and 7 ), aligning with evidence that catalytic activation of TRPC6, similarly implicated with proliferation and inflammatory responses in breast cancer, attenuates MDA-MB-231 breast cancer cell viability and migratory capacity ( 51 ). Both studies further demonstrated reductions in breast cancer cell invasiveness in response to activation of either TRPC1 (PEMF exposure) ( Figure 7D ) or TRPC6 (Furin inhibition) ( 51 ). Moreover, TRPC1 channel expression is greater in the highly metastatic MDA-MB-231 cell line compared to the less invasive MCF-7 cell line ( Figure 5E ) ( 52 ).…”
Section: Discussionsupporting
confidence: 79%
“…SOCE has been reported to play an essential role in the development of a variety of breast cancer hallmarks, including cell viability, migration, proliferation, and apoptosis resistance [22][23][24][25]. STIM1 and Orai1 are the key elements in SOCE but several proteins, such as SARAF and EFHB, play an important role fine-tuning the amount of Ca 2+ entering the cell through the store-operated channels [13,14,16,17].…”
Section: Discussionmentioning
confidence: 99%
“…Cells were routinely maintained in Dulbecco’s minimal essential medium (DMEM) (Gibco, Saint Aubin, France) supplemented with 10% heat-inactivated fetal bovine serum (FBS), 1% sodium pyruvate, 0.1 mg/mL streptomycin, 100 U/mL penicillin at 37 °C in a 5% CO2-humidified atmosphere. For SW480, SW620, CT26, HT-29 tumorsphere formation mimicking CSCs phenotype, as previously described [ 32 ], cells were cultured in DMEM/F-12 supplemented with N2, B27 supplements (Thermo Fisher Scientific, Waltham, MA, USA), and growth factors [20 ng/mL basic fibroblast growth factor (bFGF) and 20 ng/mL epidermal growth factor (EGF)] (Sigma, St. Louis, MO, USA) in a 96-well round bottom plate that facilitated the production of homogeneous spheroids of cells.…”
Section: Methodsmentioning
confidence: 99%
“…Previously, the inhibition of the convertases in CSCs was associated with upregulated expression of various metallothioneins known as tumor suppressor genes, of which the loss in colon cancer patients was associated with bad prognosis [ 31 ]. On the other hand, Furin was reported to interfere with calcium mobilization [ 29 , 32 ], and PCs repression reduced the malignant phenotype of cancer cells and resistance to apoptotic agents [ 29 ]. As a result, in recent years, the concept of CSCs has interesting implications in the exploration of new and effective therapies that target the altered signaling pathways of CSCs.…”
Section: Introductionmentioning
confidence: 99%